Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae) - Dow, Rory A.; Reels, Graham T. (Zootaxa, 2018)
Drepanosticta adenani sp. nov. (holotype ♂, from a tributary of Sungai Jela, Nanga Segerak area, Lanjak Entimau Wildlife Sanctuary, Sri Aman Division, Sarawak, Malaysian Borneo, 18 vii 2016, deposited in the Natural History Museum, London) is described from both sexes.